2021
DOI: 10.1002/mc.23297
|View full text |Cite
|
Sign up to set email alerts
|

N6‐Methyladenosine (m6A) readers are dysregulated in renal cell carcinoma

Abstract: N6‐Methyladenosine (m6A) is the most common modification of messenger RNA (mRNA) in mammals. It critically influences RNA metabolism and plays an essential role in virtually all types of bioprocesses including gene expression, tissue development, self‐renewal and differentiation of stem cells, stress response and circadian clock control. It plays a crucial role in carcinogenesis and could be used as a prognostic and a diagnostic tool and as a target for new anticancer therapies. m6A modification is dynamically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
(97 reference statements)
0
18
0
Order By: Relevance
“…It is known as m 6 A modification closely related to RNA splicing, localization, stability, export, RNA-protein interactions, alternative polyadenylation, and translation [11][12][13]. e cellular m 6 A methylation is mediated by a group of regulatory enzymes including "writers" Wilms' tumor 1-associated protein (WTAP), methyltransferase-like 3 (METTL3) and METTL14, "erasers" fat mass and obesity-associated protein (FTO) and alkB homolog 5 (ALKBH5), and "readers" YTH domain containing 1 (YTHDC1/2) and YTH N 6 -methyladenosine RNA binding protein 1/2/3 (YTHDF1/ 2/3) [14][15][16]. Generally, m 6 A methylation is increased by writers, erased by FTO or ALKBH5, and deciphered by YTHDF1/2/3 or YTHDC1/2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known as m 6 A modification closely related to RNA splicing, localization, stability, export, RNA-protein interactions, alternative polyadenylation, and translation [11][12][13]. e cellular m 6 A methylation is mediated by a group of regulatory enzymes including "writers" Wilms' tumor 1-associated protein (WTAP), methyltransferase-like 3 (METTL3) and METTL14, "erasers" fat mass and obesity-associated protein (FTO) and alkB homolog 5 (ALKBH5), and "readers" YTH domain containing 1 (YTHDC1/2) and YTH N 6 -methyladenosine RNA binding protein 1/2/3 (YTHDF1/ 2/3) [14][15][16]. Generally, m 6 A methylation is increased by writers, erased by FTO or ALKBH5, and deciphered by YTHDF1/2/3 or YTHDC1/2.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, growing evidences indicated that m 6 A dysregulation plays critical roles in tumorigenesis and cancer progression through diverse molecular mechanisms [14][15][16][17][18]. Meanwhile, the expression level of m 6 A-related regulatory proteins has been shown to be critically involved in tumorigenesis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…m6A readers with known relevance to BC, their cellular location, and molecular functions are summarized in Table 3. These m6A readers have been shown to play a role in embryonic stem cell fate (Batista et al 2014, Lasman et al 2020) energy homeostasis (Edupuganti et al 2017), human circadian rhythm (Robinson et al 2019), and various cancers (Jing et al 2021, von Hagen et al 2021. Evidence suggesting that the dysregulation of m6A readers plays a pivotal role in BC progression will be described below.…”
Section: Rna-binding Proteins As M6a Readersmentioning
confidence: 98%
“…It is estimated that in 2021 approximately 76,080 new cases would be identified in the United States and approximately 80% of the renal cancer are clear cell renal carcinoma [ 19 ]. Hagen et al performed a single-center study by analyzing the tissue samples from patients who underwent radical or partial nephrectomy at the Department of Urology at the University Hospital Bonn and reported that YTHDC1 was significantly downregulated in clear cell renal carcinoma compared to normal tissue in both mRNA and protein level [ 44 ]. Moreover, the dysregulated expression of YTHDC1 was associated with worse outcome, demonstrating that YTHDC1 may have the potential role as a biomarker and target for cancer treatment.…”
Section: Role Of Ythdc1 In Cancers and Other Diseasesmentioning
confidence: 99%